Electronic HRM: four decades of research on adoption and consequences - Bondarouk, Tanya; Parry, Emma; Furtmueller, Elfi (Taylor and Francis, 2016)
Despite the existence of a number of recent reviews of e-HRM research, we still lack a comprehensive understanding of the factors affecting the adoption and consequences of e-HRM. This paper therefore provides a review of four decades of research in this area with the aim to provide a summary and integrative framework as a basis for future research. We found that the factors affecting the adoption of e-HRM can be divided into three areas: technology; organization; and people – we refer to this as the ‘TOP’ framework. In line with we divide consequences into those that are operational, relational and transformational. We also found that there has been a shift both in the goals for e-HRM, from efficiency to improved HR service provision and the strategic reorientation of HR departments; but also that the type of consequences that the literature focuses on has also changed from operational effects, to relational and then transformational outcomes. The paper discussed these shifts in some detail, along with the implications for future research and practice.
Keywords: Electronic human resource management; e-HRM; implementation; consequences; effectiveness; literature review; e-HRM adoption